2011
DOI: 10.1016/j.bpj.2011.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Position Effects Are Linked to Sir2-Mediated Variation in Transcriptional Burst Size

Abstract: Gene expression noise varies with genomic position and is a driving force in the evolution of chromosome organization. Nevertheless, position effects remain poorly characterized. Here, we present a systematic analysis of chromosomal position effects by characterizing single-cell gene expression from euchromatic positions spanning the length of a eukaryotic chromosome. We demonstrate that position affects gene expression by modulating the size of transcriptional bursts, rather than their frequency, and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
1
30
1
Order By: Relevance
“…Since none of the isolated strains showed multimodal distributions and almost all of our promoters have at least 75% of their reads within a single distribution peak, we do not expect that this filter removed a considerable number of promoters that derive true multimodal expression distribution; however, removing this filter is advised if the tested promoters may produce such distributions. Fifth, since in our method the promoters are integrated into plasmids in a fixed position, we do not measure the effect of the local chromatin structure on the promoter function (Batenchuk et al 2011). It would be interesting to investigate this effect by measuring the function of our set of promoters in various genomic contexts.…”
Section: Dna-encoded Determinants Of Transcription Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Since none of the isolated strains showed multimodal distributions and almost all of our promoters have at least 75% of their reads within a single distribution peak, we do not expect that this filter removed a considerable number of promoters that derive true multimodal expression distribution; however, removing this filter is advised if the tested promoters may produce such distributions. Fifth, since in our method the promoters are integrated into plasmids in a fixed position, we do not measure the effect of the local chromatin structure on the promoter function (Batenchuk et al 2011). It would be interesting to investigate this effect by measuring the function of our set of promoters in various genomic contexts.…”
Section: Dna-encoded Determinants Of Transcription Noisementioning
confidence: 99%
“…In addition, the local chromatin structure of the gene may also affect its level of expression noise (Batenchuk et al 2011). One way to isolate this effect is to integrate the tested promoter upstream of a reporter gene and within a fixed genomic context.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…The burst frequency from an episodic gene, or the number of bursts of transcription that occur at that gene per cell cycle, reflects the promoter activation rate and may also vary from cell to cell. Recent studies have demonstrated both constitutive and episodic gene expression exist across organisms (14)(15)(16)(17). One emerging theme is that chromosomal context matters.…”
Section: Stochastic Events and Chromatinmentioning
confidence: 99%
“…One emerging theme is that chromosomal context matters. For instance, the site of integration of reporter genes across chromosome III in budding yeast influences the burst size of their transcriptional activity, and this may be modulated by histone deacetylation (16). Less widely explored, however, is how chromatin context and stochastic gene expression intersect to influence cell fate decisions (18).…”
Section: Stochastic Events and Chromatinmentioning
confidence: 99%
“…However, it is uncertain how applicable these findings are to bacteria, given their different mechanisms of transcription and translation. Furthermore, bacteria have different chromosome structures (Rocha 2008) and lack histones, which are largely responsible for position effects on gene silencing (Brand et al 1985) and gene expression noise in eukaryotes (Batenchuk et al 2011). Given that gene clustering is common, any effect it has on gene expression could have a major impact on analyses of gene regulation and the construction of synthetic gene circuits.…”
mentioning
confidence: 99%